Status of Reservoir Fisheries in Batang Ai Hydroelectric Dam, Sri Aman, Sarawak - Nazhatul Nazereen, Binti Rosli (Universiti Malaysia Sarawak (UNIMAS), 2014)
A study was carried out to document the status of reservoir fisheries including water quality and fish fauna at Batang Ai Reservoir due to the lack of published information. Twelve sampling stations were selected for fish and water sample collection. Results shows that depths in the study stations ranged from 20 to 110 m and pH values ranged from 5.73 to 7.92. Water temperature ranged from 26.3 to 31.13 oC, and was in decreasing trend as depth increased. DO concentrations at all stations were above 7 mgIL. Chlorophyll-a value was the highest at 20 m depth at station 10 and lowest at sub-surface of station 9. A total of 8 families represented by 17 species of fish were caught from the reservoir. The most dominant family in tenns of the number of individuals caught is Cyprinidae. Barbonymus schwanenfeldii is the most dominant species with the highest number of individuals caught. Length-weight relationship of the three species in the reservoir shows b value ranging from 2.79 to 2.88 which indicate that the fish has negative allometric growth Gonadal Somatic Index (GSI) ranged from 1.09 to 3.24. The average fisheries production in the reservoir range from 17.12 to 20.55 kg ha-1 yr-l. Therefore, proper management of the reservoir should be done to sustain the fisheries production in Batang Ai Hydroelectric Dam, Sarawak.